(untitled) (International Journal of Engineering and Computer Science, 2014)
Video surveillance systems are becoming increasingly important for crime investigation and the number of cameras installed in public space is increasing. However, many cameras installed at fixed positions are required to observe a wide and complex area. In order to efficiently observe such a wide area at lower cost, mobile robots are an attractive option. According to the result of moving object detection research on video sequences, the movement of the people is tracked using video surveillance. The moving object is identified using the Background subtraction. The Background subtraction will compare the current frame with the previous frame. The threshold value is calculated to find the moving image. Using threshold value the detected pixel is identified. Hence the movement of the object is identified accurately. The motion detection is done using Cauchy distribution model and Absolute Differential Estimation .Absolute Differential Estimation is used to compare the background frame and incoming video frame if any changes occur in incoming video frame .Cauchy distribution Model is used to detect the pixel of moving object in the detected incoming video frame. Whenever motion detected that image is saved on the server and the server will notify the Google server. The Google server will send a GCM Alert to the android application user mobile who are all registered for that application